2019
DOI: 10.1073/pnas.1900420116
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent manufacturing processes lead to a new class of inverse problems

Abstract: The control of time-dependent, energy beam manufacturing processes has been achieved in the past through trial-and-error approaches. We identify key research gaps and generic challenges related to inverse problems for these processes that require a multidisciplinary problem-solving approach to tackle them. The generic problems that we identify have a wide range of applications in the algorithmic control of modern manufacturing processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The optimisation of such processes is typically time-consuming, especially if based on complex multi-physics models. To circumvent this problem, Axinte and Billingham [267] postulated an inverse problem-solving approach, where the input is a targeted surface to be created (e.g., laser polished), and the outputs are control parameters needed to achieve this surface. The extent to which the inverse-problem approach is adopted by researchers in the field is still limited, as the majority of beam modelling/optimisation approaches continue to be trial-and-error.…”
Section: Discussionmentioning
confidence: 99%
“…The optimisation of such processes is typically time-consuming, especially if based on complex multi-physics models. To circumvent this problem, Axinte and Billingham [267] postulated an inverse problem-solving approach, where the input is a targeted surface to be created (e.g., laser polished), and the outputs are control parameters needed to achieve this surface. The extent to which the inverse-problem approach is adopted by researchers in the field is still limited, as the majority of beam modelling/optimisation approaches continue to be trial-and-error.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown for other dwell-time energy beam processes (e.g. waterjet milling, pulsed laser ablation, focused ion beam) [43][44][45][46], that the solution to the Inverse Heat Placement Problem does not usually consist of simple linear paths and significant scientific, engineering and mathematical challenges must be dealt with to make progress.…”
Section: Introductionmentioning
confidence: 99%
“…Axinte et al [ 35 ] demonstrated that, despite differences in their nature, many energy beam (EB) controlled-depth machining processes could be modelled using the same mathematical framework in the study of freeform surfaces machining. They have developed approaches and algorithms for the inverse problem to generate freeform surfaces using different EB machining processes and various workpiece target materials [ 36 ]. Wan et al [ 37 , 38 ] proposed a time-variant and space-variant tool influence function (TIF) model in the study of precision optical polishing.…”
Section: Introductionmentioning
confidence: 99%